CompTIA Mobility+ certification : exam guide (exam MB0-001) - Rogers, Bobby E. (All-in-one (Series), 2014)
A new exam guide for the new certification on mobile computing technologies from CompTIA Prepare for CompTIA Mobility+ exam MB0-001 with McGraw-Hill Professional--a Platinum-Level CompTIA Authorized Partner offering Authorized CompTIA Approved Quality Content to give you the competitive edge on exam day. Get complete coverage of all objectives for CompTIA Mobility+ exam MB0-001 from this comprehensive resource. Written by an information security engineer, this authoritative guide fully addresses the skills and technologies required to successfully deploy, integrate, support, and mange a mobile environment. You'll find learning objectives at the beginning of each chapter, exam tips, practice exam questions, and in-depth explanations. Designed to help you pass this challenging exam, this definitive volume also serves as an essential on-the-job reference. Covers all exam topics, including: Networking concepts and the OSI model Network infrastructure and technologies Radio frequency principles Cellular technologies Wi-Fi client technologies Planning for mobile devices Implementing mobile device infrastructure Mobile security risks Mobile security technologies Troubleshooting network issues Monitoring and troubleshooting mobile security Troubleshooting client issues Electronic content includes: 200 practice exam questions Test engine that provides full-length practice exams and customized quizzes by chapter or by exam domain Save 10% on CompTIA exam vouchers for any CompTIA certification! See inside for details.